Telaah Konsep Pendidikan Islam dalam Perspektif Hadis - Dewi Masitoh (Jurnal Ilmiah Edukatif, 2023)
This research aims to explore the concept of Islamic education from a hadith perspective in the context of a hadith course. Islamic education is an integral aspect in forming Muslim individuals who are full of religious and moral understanding. In this effort, the hadiths of the Prophet Muhammad SAW have a central role in providing guidelines and principles that are relevant for education. This research conducted a survey of a number of hadiths related to education from primary sources, including Sahih Bukhari and Sahih Muslim. Through diligent analysis, we identified the main concepts emerging from these hadiths which are closely related to Islamic education. The results of this research reveal a variety of educational values, methods and principles that can be applied in the context of Islamic education. An in-depth approach to these hadiths in studying hadith courses provides a deeper understanding of how the Prophet Muhammad SAW taught religion and ethics to his people. The concepts of Islamic education taken from the perspective of this hadith provide a solid basis for developing more effective curriculum and teaching methods in Islamic religious education.